Seasonal variation of the Beaufort shelfbreak jet and its relationship to Arctic cetacean occurrence. Issue 12 (2nd December 2016) - Lin, Peigen; Pickart, Robert S.; Stafford, Kathleen M.; Moore, G. W. K.; Torres, Daniel J.; Bahr, Frank; Hu, Jianyu
Abstract: Using mooring time series from September 2008 to August 2012, together with ancillary atmospheric and satellite data sets, we quantify the seasonal variations of the shelfbreak jet in the Alaskan Beaufort Sea and explore connections to the occurrences of bowhead and beluga whales. Wind patterns during the 4 year study period are different from the long‐term climatological conditions that the springtime peak in easterly winds shifted from May to June and the autumn peak was limited to October instead of extending farther into the fall. These changes were primarily due to the behavior of the two regional atmospheric centers of action, the Aleutian Low and Beaufort High. The volume transport of the shelfbreak jet, which peaks in the summer, was decomposed into a background (weak wind) component and a wind‐driven component. The wind‐driven component is correlated to the Pt. Barrow, AK alongcoast wind speed record although a more accurate prediction is obtained when considering the ice thickness at the mooring site. An upwelling index reveals that wind‐driven upwelling is enhanced in June and October when storms are stronger and longer‐lasting. The seasonal variation of Arctic cetacean occurrence is dominated by the eastward migration in spring, dictated by pack‐ice patterns, and westward migration in fall, coincident with the autumn peak in shelfbreak upwelling intensity. Key Points: Patterns of alongcoast winds in the Beaufort Sea have shifted in recent years due to regional atmospheric centers of action Wind‐driven transport of the shelfbreak jet and upwelling are enhanced in June and October when storms are stronger and longer‐lasting Seasonal variation of cetacean occurrence near the shelfbreak jet is impacted by pack‐ice cover and upwelling